IMPLEMENTATION OF ONLINE ARABIC LEARNING IN THE NEW NORMAL ERA IN MADRASAH ALIYAH NEGERI 1 MUARO JAMBI - Muhammad Sobri; Mutia Annisa; Eva Iryani (The Islamic Education and Multiculturalism Foundation, 2020)
Abstract: This study aims to describe the implementation of online-based Arabic learning in the new normal era at MAN 1 Muaro Jambi. This research was conducted at MAN 1 Muaro Jambi in January-March 2021. This type of research was descriptive qualitative with phenomenological research type. The data from this study were obtained through observation, interviews and documentation as supporting data from the results of observations and interviews. The results of this study indicated that the implementation of online-based Arabic learning was carried out quite well, namely before the implementation of learning the teacher makes a lesson plan. In practice, the teacher used the madrasah e-learning application and whatsapp, the method used was the lecture and assignment method, The media used were pdf and photos of learning materials, the assessment carried out was an integrative assessment, which was a combination of knowledge, attitudes, and skills assessments. However, there were obstacles in the implementation of online-based Arabic learning, where there were students who did not have a device, the inability of students to buy quotas, the unstable internet network, there were many tasks that given by the teacher, the teacher found it was difficult to observe student development, and the lack of learning methods. The supporters of the implementation of online-based Arabic learning were the provision of free learning quota subsidies for students who did not have a device to ride with their friends or make assignments to madrasah so that there was an increase in the quality of teachers in utilizing technology.